PENGARUH KOMPETENSI DOSEN DAN FASILITAS BELAJAR TERHADAP KEPUASAN MAHASISWA PENDIDIKAN EKONOMI FKIP UNS - Mutmainah Isnaini; Dewi Kusuma Wardani; Leny Noviani (Department of Economics Education, Universitas Sebelas Maret, 2018)
The objective of research were to find out the effect of lecturers’ competencies and learning facilities on students’ satisfaction of economic education FKIP UNS. The method used quantitative method . The sample were 171 students’ trade system Forces Economic Education FKIP. The data collection techniques used questionnaires. The data were analyzed by using multiple regression analysis. The results showed that there was a significant positive effect of lecturers’ competencies and learning facilities variables on students’ satisfaction of economic education FKIP UNS. The magnitude of the effect of lecturers’ competencies and learning facilities variables toward students’ satisfaction simultaneously obtained from the calculation of the R-square of 70,4%.